AB0770 Rheuma-card: involvement of the patient through a secure systems access into the treat to target strategy in rheumatology. (23rd January 2014) - Ferraccioli, G.; Salaffi, F.; Lapadula, G.
Abstract : Background: Computer technology and Internet access are becoming increasingly available. A recent report published by the National Institute of Statistics showed at the end-2011 that 58.7% of Italian families (35.800.000) had a personal computer (slightly higher than the 57.6% in 2010); from 2006 to 2011 a significantly increased proportion of households had a fast connection to access the Internet from home (14.4 percent in 2006 to 45.8 percent in 2011). Objectives: The RHEUMA-CARD (Complete Access to Rheumatologic Data) is a project, specifically designed to address the problem of enabling secure access to health information through Internet, not just for healthcare providers and medical personnel, but also for patients to view their own medical records and judge on the outcomes reached with their rheumatologists. Methods: The project is using familiar Web technologies to support the search and retrieval of clinical information, of the GISEA registry. The GISEA registry is an independent database, established by the Italian Group for the Study of Early Arthritis (GISEA) in 2008, designed for collecting long-term follow-up data concerning patients with rheumatic diseases treated with biological agents in order to investigate the realworld characteristics in terms of disease activity, comorbidities and survival on treatment (1 ). Results: The GISEA registry contains up to now more than 7000 patients (Table 1 ) Conclusions: The proposed method for Internet-based exchange of patient data is particularly useful for cooperative healthcare and the creation of lifetime healthcare records. RHEUMA-CARD is designed to give patients as well as providers access to personal health records via Internet in order to reach the major outcomes. References: Lapadula G et al. Reumatismo. 2011;63:155-64 Disclosure of Interest: None Declared